From Relics to Remains: Wordsworth’s “The Thorn” and the Emergence of Secular History - Rzepka, Charles (Romanticism on the Net, 2003)
AbstractIn their recurrent focus on the relationship between narrative and experience, “testimony” and “relics,” the Lyrical Ballads show Wordsworth to be our first truly archaeological poet, the first to take seriously the notion of “pre-history” as a mode of encountering the material world in the present, and not just a way of designating a material world that pre-dates written records. Wordsworth’s reading in Druid history, and specifically William Stukeley’s accounts of barrow excavations near Stonhenge and Avebury, helped to shape the poet’s understanding of “pre-history” in this sense. “The Thorn”, with its reiterations of measurement and spatial orientation relative to the site of a mound that may or may not be “an infant’s grave,” reflects the specific influence of Stukeley’s accounts, as well as Wordsworth’s preoccupation with the mystery of how whatever “remains” in the present manages to make present, in the space and time of a universal history, the historian or poetic “pre-historian” who has encountered it.